AN OVERIVEW OF TOMATO JUICE ADMINISTRATION ON BLOOD PRESURE REDUCTION IN ELDERLY PATIENTS WITH HYPERTENSION IN GEMURUH VILLAGE - Luthfi Nafisa Agustina; Dwi Astuti; Wiwik Priyatin (PT. Jurnal Center Indonesia Publisher, 2025)
Background: Hypertension is a common non-communicable health problem among the elderly and poses a risk of serious complications. Nonpharmacological therapy using tomato juice—which is rich in potassium and lycopene—has the potential to naturally lower blood pressure. Objective: To observe the changes in blood pressure in elderly patients with hypertension following the administration of tomato juice. Method: A case study design involving one elderly respondent (78 years old) with mild hypertension. The intervention consisted of administering 200 ml of tomato juice every morning before meals for 7 consecutive days. Blood pressure was measured every morning before and after consuming the juice. Results: There was an average reduction of 7.4 mmHg in systolic blood pressure and 5.4 mmHg in diastolic blood pressure after 7 days of intervention, indicating a positive effect of tomato juice in lowering blood pressure. Conclusion: Daily administration of tomato juice for 7 days effectively reduced blood pressure in an elderly hypertensive individual, suggesting it as a safe and practical non-pharmacological therapy.